Talasoterapia. Revisión de los artículos científicos publicados en los últimos 20 años - Cerrada Fernández-clemente, Alberto (Anales de Hidrología Médica, 2008)
Objectives: Review articles published in the last 20 years related to thalassotherapy and sea water. Method: Several sources of information have been used specially from medline, trip database, the cochrane library, dare…, with different key words in the main idioms. We have classified the articles by subject. Results: Main subjects are related to dermatology followed by rheumatology, ORL and respiratory, infections, sea products, pediatrics, cardiovascular, deep sea water and stress. Most of them are clinical trials, followed by revisions, letters or editorials, historicals and case reports. The origin is mainly from Europe (Russia, Germany, France, Italy, UK, Spain…) followed by Israel, Japan and USA. Notable among them are Dead Sea studies from Israel demonstrating beneficious effects in dermatology and rheumatology. Increasing of deep sea water studies from Japan linked to improvement of health. Studies from USA are related to sea products and good results in cancer and immunology. Articles related to ORL show the improvement of application of sea water in this pathology.
Keywords: Thalassotherapy; Sea water therapy; Balneotherapy sea cure; Rheumatology; Spa sea; Dermatology sea